2015
DOI: 10.1002/jsfa.7231
|View full text |Cite
|
Sign up to set email alerts
|

Selenium (Se) improves drought tolerance in crop plants – a myth or fact?

Abstract: Climate change has emerged as one of the most complex challenges of the 21st century and has become an area of interest in the past few decades. Many countries of the world have become extremely vulnerable to the impacts of climate change. The scarcity of water is a serious concern for food security of these countries and climate change has aggravated the risks of extreme events like drought. Oxidative stress, caused by a variety of active oxygen species formed under drought stress, damages many cellular const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 118 publications
(194 reference statements)
0
40
0
Order By: Relevance
“…More than 60% of Iranian lands is located in the arid and semi-arid regions in which, water scarcity is the most important limiting factor for agricultural activities (Modarres & de Paulo Rodrigues da Silva 2007). Studies have shown that under water deficit condition, oxidative stress reduces plant growth, respiration, and photosynthesis through damaging cellular compounds, such as carbohydrates, lipids, nucleic acids, and proteins (Ahmad et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More than 60% of Iranian lands is located in the arid and semi-arid regions in which, water scarcity is the most important limiting factor for agricultural activities (Modarres & de Paulo Rodrigues da Silva 2007). Studies have shown that under water deficit condition, oxidative stress reduces plant growth, respiration, and photosynthesis through damaging cellular compounds, such as carbohydrates, lipids, nucleic acids, and proteins (Ahmad et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Selenium at low concentrations exerts positive effects for plants such as promoting growth, increasing antioxidative capacity, improving yield and quality, and delaying ripening and senescence (Hartikainen et al, 2000; Xue et al, 2001; Turakainen et al, 2004; Broadley et al, 2010; Pukacka et al, 2011; Pezzarossa et al, 2012). Applying Se fertilizer as base fertilizer or foliar spray has been used to increase the Se content in the edible portion of crops and to simultaneously counteract the detrimental effects of diverse environmental stresses, such as heavy metals, water, drought, salt, high temperature, UV radiation, senescence, pathogens, and insect pests (Hartikainen et al, 2000; Pennanen et al, 2002; Hanson et al, 2003; Djanaguiraman et al, 2005, 2010; Germ et al, 2005; Broadley et al, 2010; Yao et al, 2010; Zembala et al, 2010; Hasanuzzaman and Fujita, 2011; Hasanuzzaman et al, 2011; Pukacka et al, 2011; Kumar et al, 2012; Pezzarossa et al, 2012; Feng et al, 2013; Ardebili et al, 2014; Ahmad et al, 2016; Kaur et al, 2016; Wu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Since changes of the chlorophyll-to-carotenoid ratio can indicate water deficient conditions (Jaleel et al, 2009; Ramakrishna and Ravishankar, 2011), the higher ratio in EVOO from the NDS-NT group as compared to the DS-NT one, and from the DS-T group as compared to the DS-NT one, might confirm the capacity of Se to protect plants from drought stress damage (Hasanuzzam et al, 2010; Proietti et al, 2013; Ahmad et al, 2016). In fact, Se has protective effects on chloroplast enzymes with a consequent increase in photosynthetic pigment biosynthesis (Pennanen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%